2015
DOI: 10.1075/lia.6.1.02mcm
|View full text |Cite
|
Sign up to set email alerts
|

Subjunctive use and development in L2 French

Abstract: We investigated the use and development of the Subjunctive in L2 French. Participants were 29 students of French at a UK university, who additionally spent nine months in France, and ten native speakers of French. Data were collected from two production tasks (oral and written) and a grammaticality judgement task. The results show that all participants made some use of the Subjunctive before leaving for France, with only limited development in its use during their stay. It is more frequently used in writing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Such findings suggest that both groups had knowledge of the obligatory subjunctive that coincided with the expected norms, with proficiency further strengthening this knowledge among L2 speakers. These findings are therefore consistent with previous research on the L2 acquisition of the French subjunctive (see, e.g., Ayoun 2013;Bartning et al 2012;Howard 2008;McManus and Mitchell 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such findings suggest that both groups had knowledge of the obligatory subjunctive that coincided with the expected norms, with proficiency further strengthening this knowledge among L2 speakers. These findings are therefore consistent with previous research on the L2 acquisition of the French subjunctive (see, e.g., Ayoun 2013;Bartning et al 2012;Howard 2008;McManus and Mitchell 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Exploring the L2 acquisition of the French subjunctive by L1 British speakers is a pertinent test case, given the morphosyntactic differences between English and French, which we will discuss in the following section. Furthermore, although many studies have explored the various factors contributing to this developmental delay, including the deterministic role of proficiency (Ayoun 2013;McManus and Mitchell 2015), licensing conditions/trigger type (Ayoun 2013;McManus and Mitchell 2015;Bartning 2008;Howard 2008), and the role of learning context (McManus and Mitchell 2015;Howard 2008), very few have directly considered the role of L1 influence. Although Ayoun (2013) did not directly explore L1 influence, she did investigate L2 learners' knowledge of the subjunctive according to the lexical-semantic properties of the matrix predicate and found that L2 learners performed most accurately with order/interdiction (i.e., directive) predicates in comparison to judgment, emotion, wish/regret, and doubt/impossibility predicates, despite the relative infrequency of directive predicates in the input (see, e.g., Kastronic 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that McManus and Mitchell (2015) report similar findings with Anglophone learners who had spent nine months abroad and who completed two production tasks (a written argumentative task and an oral, guided interview) and a grammaticality judgment task.…”
Section: Literature Review Of French Tam Studiessupporting
confidence: 57%
“…Other studies also found that L2 learners were highly accurate for the indicative present, but not the subjunctive e.g., (Herschensohn and Arteaga 2009;Howard 2008Lealess 2005;McManus and Mitchell 2015). For instance, the longitudinal case study of Billy-an Anglophone learner who started acquiring French in an instructed setting at 14 in Ayoun (2015)-reveals an interlanguage grammar with contrasts and systematicity between different temporalities and with the indicative-subjunctive alternation, but again, accuracy percentages were noticeably better on guided production tasks than on some elicitation tasks such as sentence completion tasks.…”
Section: Literature Review Of French Tam Studiesmentioning
confidence: 91%
“…In contrast, studies examining the impact of SA on the acquisition of specific grammatical features of the L2 have provided mixed results when comparing groups of SA and at‐home (AH) learners, and a number of studies have demonstrated that the AH learning context may be equally beneficial to the L2 acquisition of categorical grammatical features (Arnett, 2013; Collentine, 2004; Howard, 2005, 2008; Isabelli–García, 2010). More recent results from the LANGSNAP project (McManus & Mitchell, 2015; Mitchell et al., 2017) also indicate that even a full academic year in the TL may not predict significant gains in grammatical accuracy, or may predict gains in some grammatical structures but not all. For example, the L2 French learners in this study demonstrated gains in accuracy rates for the oral production of two past tense verb forms, but not for the use of the subjunctive mood, during and following a 1‐year period of SA in France.…”
Section: The Impact Of Study Abroad: Oral Proficiency and Grammatical...mentioning
confidence: 99%